Bangladesh in Bondage - Khan, Q M Jalal. author. aut Link
XXIII, 185 p. 2 illus.
Keywords: This book brings together a collection of essays about the untenable political status quo in Bangladesh under Sheikh Hasina. Since democratization in the 1990s, Bangladeshi political life has been characterized by fierce battles over the role of religion in society, corruption, and the obstacles to constructing a society with freedom of expression and rule of law, independent from the influence of powerful neighboring countries. Academic freedom and other human rights issues have hindered the study of Bangladesh heretofore, and corruption, police abuses, and election rigging are common as well as widely documented. In this passionate, sometimes personal exploration of the issues of social justice, rule of law, and the democratic process in Bangladesh, the book offers a valuable case study of how an Asian developmental state is otherwise regressing backwards morally, socially, and politically. The Bangladeshi struggle for sovereignty, prosperity and democracy documented in this bookwill be of interest to political scientists, scholars of South Asia, and those of Islam. Dr Q M Jalal Khan is author of Bangladesh: A Divided Country and Bangladesh Divided: A Corrupt Police and Prison State. His work, “Sheikh Hasina’s Brutal BNP-Phobia and Her Scandalous ‘Midnight’ Power Grab Through Vampire Vote Dacoity and Villainous ‘S/Election’ Rigging with an All-Time High Record of Humongous White-Collar Corruption” has appeared in Bangladesh: A Suffering People Under State Terrorism. His co-edited Begum Khaleda Zia: People's Leader of Bangladesh and India’s Hegemonic Design in Bangladesh are among his more recent volumes. Forthcoming is his co-edited Zia, the Legend of Bangladesh. American-educated Dr Khan’s numerous other publications include his literary criticism in books and articles.